Design compact microstrap patch antenna with T-shaped 5G application - Ali Abdulateef Abdulbari; Mustafa Mohammed Jawad; H. O. Hanoosh; Murtaja Ali Saare; Saima Anwar Lashari; Sari Ali Sari; Sarosh Ahmad; Yaser Khalill; Yaqdhan Mahmood Hussain (Institute of Advanced Engineering and Science, 2021)
This paper is presents a microstrap patch with a T-shaped rectangular antenna workings; the T-shaped patch operating at 3.6 GHz resonating frequency range for 5G application (from 2.9 to 4.4 GHz) repectively. The overall size of the proposed antenna is 22×24×0.25 mm3; the feeding technique using a 50 Ω feed line to the antenna. The proposed antenna is printed on compact Rogers RT 588 lz substrate having permittivity (ɛr) 2.00, loss tangent (tan δ) 0.0021, with thikness 0.2 mm. The proposed antenna introducesmany advantages like small size, low profile, and simpler structure. The characteristics such as radiation pattern, reflection coefficient, gain, current distribution, and radiation efficiency are respectively presented and discussed, using CST microwave study in simulating and analysing. Introducing a slot with a rectangular T-shaped patch antenna achieved lower frequency with 98.474% radiation efficiency and peak gain of the proposed antenna at 2.52 dB. The fractional bandwidth is 42.81% (2.90 GHz to 4.48 GHz) with a resonant frequency of 3.6 GHz and return loss at 28.76 dB. This frequency band attributessuited 5 G mobile application.